Anticancer Effects of ZnO/CNT@Fe3O4 in AML-Derived KG1 Cells: Shedding Light on Promising Potential of Metal Nanoparticles in Acute Leukemia - Yousefi Amir-Mohammad; Pourbagheri-Sigaroodi Atieh; Fakhroueian Zahra; Salari Sina; Fateh Kosar; Momeny Majid; Bashash Davood (Tehran University of Medical Sciences, 2022)
Background: Therapeutic approaches for acute myeloid leukemia (AML) have remained largely unchanged for over 40 years and cytarabine and an anthracycline (e.g., daunorubicin) backbone is the main induction therapy for these patients. Resistance to chemotherapy is the major clinical challenge and contributes to short-term survival with a high rate of disease recurrence. Given the established efficacy of nanoparticles in cancer treatment, this study was designed to evaluate the anticancer property of our novel nanocomposite in the AML-derived KG1 cells.
Materials and Methods: To assess the anti-leukemic effects of our nanocomposite on AML cells, we used MTT and trypan blue assays. Flow cytometric analysis and q-RT-PCR were also applied to evaluate the impact of nanocomposite on cell cycle and apoptosis.
Results: Our results outlined that ZnO/CNT@Fe3O4 decreased viability and metabolic activity of KG1 cells through induction of G1 arrest by increasing the expression of p21 and p27 cyclin-dependent kinase inhibitors and decreasing c-Myc transcription. Moreover, ZnO/CNT@Fe3O4 markedly elevated the percentage of apoptotic cells which was coupled with a significant alteration of Bax and Bcl-2 expressions. Synergistic experiments showed that ZnO/CNT@Fe3O4 enhances the cytotoxic effects of Vincristine on KG1 cells.
Conclusion: In conclusion, this study sheds light on the potent anti-leukemic effects of ZnO/CNT@Fe3O4 and provides evidence for the application of this agent in the treatment of acute myeloid leukemia.